高感度シングルセルRNA-seq解析TAS-Seqの肺線維症病態研究への応用 - 七野, 成之; 上羽, 悟史; 松島, 綱治 (日本薬理学会年会要旨集, 2023)
Single-cell RNA-sequencing (scRNA-seq) can obtain comprehensive gene expression information on tens of thousands of single cells and accelerate pathophysiological insights at the single cell level. However, there are many technical challenges in terms of sensitivity and accuracy. We previously developed TAS-Seq, a sensitive and accurate scRNA-seq method, but it only applicable to nanowell-based system, which limits its utility. To solve these issues, we have developed a cDNA amplification method, TAS-Seq2, which is highly sensitive and broadly applicable to various scRNA-seq platforms, including 10X Chromium and BD Rhapsody. TAS-Seq2 exerted 1.5-2 times higher gene-detection sensitivity and better cell subset separation than the original methods.Next, we analyzed silica-induced lung fibrosis using TAS-Seq, and identified C1q as a novel specific marker for interstitial macrophages (IMs). By using Ccr2-/- mice, BrdU, and parabiosis, C1q+ Lyve1- CD163- IMs increased depending on local proliferation and CCR2-independent monocytes. In addition, C1q itself induced lung fibrosis, fibroblasts/epithelial cell activation with gene-expression changes associated with fibrosis. Furthermore, in human fibrotic lungs, C1Q+ SELENOP+ IMs were found as a distinct population from SPP1+ macrophages, and C1Q+ IMs were increased in fibrotic area. These results suggest that C1Q+ IMs might exacerbate lung fibrosis by inducing fibroblast and epithelial cell activation through the production of C1q.